Chemical composition and larvicidal activity against Aedes mosquitoes of essential oils from Arisaema fargesii. Issue 2 (29th August 2019) - Huang, Yuting; Lin, Mengya; Jia, Mengmeng; Hu, Junpeng; Zhu, Liang
Abstract: BACKGROUND: Dengue fever is caused by the spread of dengue virus by Aedes mosquito vectors. Currently, the most effective way to control dengue is by preventing mosquitoes from spreading the disease. Arisaema fargesii is a Chinese herbal medicine commonly used to repel mosquitoes. In our laboratory, anti‐mosquito chemical components were extracted from A. fargesii, and the effects of these substances on mosquito larvae were examined. RESULTS: In total, 48 compounds corresponding to 98.79% of the total oil were identified and the major compounds identified were linalool (12.38%), carvacrol (8.27%), eugenol (5.21%), and β ‐selinene (5.36%). Essential oil had larvicidal activity against Ae. aegypti and Ae. albopictus with LC50 values of 40.49 mg/L, 47.01 mg/L, respectively. The LC50 values of carvacrol, eugenol, linalool and β ‐selinene were 32.78, 56.34, 70.56, 136.03 mg/L against Ae. aegypti larvae, and 39.08, 52.07, 82.34, 151.74 mg/L, respectively, against Ae. albopictus larvae. Biochemical assays of Aedes larvae showed that the activities of acetylcholinesterase (AChE), monooxygenases (MO), glutathione‐ S ‐transferase (GST), p‐Nitrophenyl acetate (p‐NPA) esterase, α ‐esterase and β ‐esterase were significantly affected by carvacrol. Essential oil induced the detoxification mechanism for the action of GST and MO. CONCLUSION: The result indicates that essential oil of A. fargesii and its isolated constituent have good inhibitory effects on the defense enzymes of Aedes mosquito larvae. A. fargesii essential oil can be used to control Aedes mosquito larvae to prevent the spread of dengue fever. © 2019 Society of Chemical Industry Abstract : This article demonstrates that the essential oil of Arisaema fargesii and its main isolated constituent have good inhibitory effects on the defense enzymes of Aedes mosquito larvae.